2018
DOI: 10.1097/md.0000000000011975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term lifestyle intervention on mild cognitive impairment in hypertensive occupational population in China

Abstract: Background:The incidence of hypertension in China is high, which seriously affects people's health, including occupational population in mining areas. Cognitive dysfunction has a serious impact on the work and life of patients. Lifestyle intervention can improve diabetes and cardiovascular diseases. However, there are few studies on the effects of lifestyle interventions on cognitive function in hypertensive patients. So the aim of this study was to analyze the effect of long-term lifestyle intervention on mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The cognitive function of the experimental group improved more than that of the control group. This was in line with the findings of a study showing that the cognitive function of middle-aged adults improved after an LSI program [ 38 ]. Yoga practice is in line with the findings that it can help prevent age-related degeneration by altering heart metabolism risk factors, autonomic function and the BDNF in healthy adults [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The cognitive function of the experimental group improved more than that of the control group. This was in line with the findings of a study showing that the cognitive function of middle-aged adults improved after an LSI program [ 38 ]. Yoga practice is in line with the findings that it can help prevent age-related degeneration by altering heart metabolism risk factors, autonomic function and the BDNF in healthy adults [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between hypertension and cognitive dysfunction has been a concern, and the mechanism of hypertension-related cognitive dysfunction remains unclear. [23] Kivipelto M et al found that in midlife vascular risk factors like hypertension, diabetes mellitus, hyperlipidemia lead to the development of mild cognitive impairment (MCI) in late life. [24] The study done by, Marijanatadic et al, also supports findings of our study, that hypertension related cognitive dysfunction develops as a result of imbalance in autoregulation of cerebral blood flow and cerebral vascular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews also concluded that multidomain interventions that combined both physical and cognitive components appeared to be more effective than the single-domain interventions in patients with MCI (20). There is limited evidence that lifestylebased interventions may help maintain or improve cognitive function in Chinese older adults with MCI (22,23). Notably, numerous studies have tested whether multidomain lifestyle and behavioral interventions may benefit cognitive function in people with MCI, but few have focused on minorities such as black older adults.…”
Section: Non-pharmacological Intervention Studies In Different Populamentioning
confidence: 99%